2022
DOI: 10.1139/cgj-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Critical insights in laboratory shear wave velocity correlations of clays

Abstract: Shear wave velocity is an important mechanical/dynamic parameter allowing the characterization of a soil in the elastic range (γ < 0.001 %). Thirty five existing laboratory correlations of small strains shear modulus or shear wave velocity were examined in this study and are grouped into different general forms based on their geotechnical properties. A database of 11 eastern Canadian clay deposits was selected and used for the critical insights. The effect of the coefficient of earth pressure at rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…Unfortunately, it has been shown that different forms of the correlation equations have been devel oped in different areas. It appears that local correl ations are necessary for satisfactory use of the technique as demonstrated for example by L'Heureux and , Duan et al (2019) or Elbeggo et al (2021). In this paper data for clays in eastern Canada will be examined and compared with similar clays in Norway and southern Sweden.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, it has been shown that different forms of the correlation equations have been devel oped in different areas. It appears that local correl ations are necessary for satisfactory use of the technique as demonstrated for example by L'Heureux and , Duan et al (2019) or Elbeggo et al (2021). In this paper data for clays in eastern Canada will be examined and compared with similar clays in Norway and southern Sweden.…”
Section: Introductionmentioning
confidence: 98%
“…The most common seismic geophysical tests performed at the ground surface are seismic refraction and surface wave measurements in multichannel arrays (MASW, SPAC), whereas the tests performed in boreholes are the downhole (DH), cross hole, and uphole tests; the DH test is one of the most commonly used. Conventionally, DH tests are performed in a vertical borehole, where the P-and S-wave travel times are measured from a surface seismic source to a geophone located at different depths within the borehole [4]. Alternatively, DH tests can be performed using a seismic cone penetrometer (SCPT) rig.…”
Section: Introductionmentioning
confidence: 99%